A Controlled Comparative Clinical Study on Navaka Kashaya and Khadira Aristadi Kashaya in the Management of Vicharchika - B C, Lavanya; Bhat, Roopa (International Research Journal of Ayurveda & Yoga, 2021)
A comparative clinical study to evaluate the therapeutic effect of Khadira aristadi Kashaya and Navaka Kashaya in the management of Vicharchika. A single blind Controlled comparative clinical study with pre test and post test design. Conducted in Dhanvantari Ayurveda medical college Hospital; Siddapur, Karnataka.40 patients suffering from Vicharchika / Dermatitis of either sex were selected for the study. Selected patients were treated under two groups; A and B. Group A with oral administration of Khadira aristadi Kashaya, in a dose of 30 ml before food twice a day with sukhoshna jala as anupana and the same is continued for 30 days. Group B with oral administration of Navaka Kashaya, in a dose of 30 ml before food twice a day with sukhoshna jala as anupana for 30 days .The response following the intervention was assessed on 1st, 15th, 21st, and 30th days to find out the progress of the Condition in both the groups. Further the change observed by the completion of the treatment was subjected to paired and unpaired t test to know the statistical significance. By using paired t test both the group parameters were statistically highly significant (P<0.001).Mean wise group A shows more improvement than group B. By Using unpaired t test: group A is showing more relief (%) in Pidaka, Kandu, Shyavata and Srava also statistically proved. In Kandu relief was statistically highly significant (P<0.001) and Pidaka and Srava statically significant (P<0.005) in these parameters. Final conclusion of this comparative clinical study is Group A is more effective than Group B (Khadira aristadi Kashaya is more effective than Navaka Kashaya) in the management of Vicharchika.